Determination of daytime clenching events in subjects with and without self‐reported clenching. (1st August 2013) - Fujisawa, M.; Kanemura, K.; Tanabe, N.; Gohdo, Y.; Watanabe, A.; Iizuka, T.; Sato, M.; Ishibashi, K.
Summary: To confirm the validity of self‐awareness of daytime clenching, specific electromyogram (EMG) characteristics of clenching behaviour were determined using surface EMG recordings. Temporal muscle EMGs were recorded for 5 h in 13 subjects with self‐reported clenching (clenching group: 27·5 ± 3·8 years old) and 12 subjects without self‐reported clenching (control group: 28·6 ± 7·1 years old). All EMG data were recorded and stored on a portable EMG apparatus. The device was similar in size to a hearing aid, and suitable to record daytime EMG without restriction of daily activities. A clenching event was defined as muscle activity exceeding 10% of the maximum voluntary contraction. Furthermore, simultaneous voice recording was also performed to identify the corresponding EMG event as functional or parafunctional. The mean number of clenching events was 192·8 ± 228·8 and 24·8 ± 26·5 in the clenching and the control groups, respectively ( P  < 0·05, Mann–Whitney U ‐test); the number of functional events was not significantly different between the groups. Because there was a significant difference in the number of clenching events between the groups, self‐reported daytime clenching is considered to be a reliable screening parameter for awake bruxism.